Co-transformation of bean callus using high-velocity microprojectiles- mediated DNA transfer - Eissa Ahmed, E.; Bisztray, Gy.; Velich, I. (International Journal of Horticultural Science, 2001)
We have found that 50 mg/I kanamycin and 0.8 Mo1/1 mannitol concentration was sufficient to kill the control callus of bean (Phaseolus vulgaris L.) and differentiate transgenic from the non-transgenic cells. The GeneBooster particle delivery system was used for the bombardment of bean callus. The kanamycin resistance gene was used as a selectable marker. The test was made by transferring the healthy white callus, subcultured for three months on selective and non-selective medium. After selection on kanamycin containing media, several kanamycin resistant calli had been obtained, survived and grew. After selection on mannitol containing media no drought resistant calli had been obtained. Resistance of the selected calli were verified by their ability to grow repeatedly on selective medium containing 150 mg/I kanamycin. Selective pressure was maintained over a period of 8 months.